2011
DOI: 10.1016/j.apmr.2011.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Pilates Method of Exercise in Healthy People

Abstract: Research studies published from inception to May 7, 2011 were selected for evaluation. Two reviewers independently applied the inclusion criteria to selected potential studies. Studies were included if they were published in a peer-reviewed journal, written in the English language, conducted as a randomized controlled trial (RCT) or quasi-RCT in healthy people, had an inactive and/or exercise control group(s), included key study outcomes, and used the PME as the study intervention in at least 1 study arm.Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
45

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 46 publications
2
82
0
45
Order By: Relevance
“…It was indeed verified that Pilates generated gain in the flexibility and muscle strength of ballet dancers 10 . However, a systematic review 11 demonstrated the scarcity of evidence on the effectiveness of Pilates over muscle resistance, flexibility, and strength. In regards to postural alignment, Cruz-Ferreira et al 11 , presented contradictory results and no evidence of the effects of the Pilates method.…”
mentioning
confidence: 99%
“…It was indeed verified that Pilates generated gain in the flexibility and muscle strength of ballet dancers 10 . However, a systematic review 11 demonstrated the scarcity of evidence on the effectiveness of Pilates over muscle resistance, flexibility, and strength. In regards to postural alignment, Cruz-Ferreira et al 11 , presented contradictory results and no evidence of the effects of the Pilates method.…”
mentioning
confidence: 99%
“…Dessa forma, o MP parece atuar de forma pontual nas principais demandas inerentes ao envelhecimento, tornando-se uma forte ferramenta de prescrição de exercício para idosos e indivíduos que buscam uma prática de atividade física regular diferenciada (32) . Os achados deste estudo e a identificação dos fatores motivacionais para a prática de atividade física de idosos contribuem na elaboração de ferramentas que atendam às expectativas deste público e auxilie na manutenção em longo prazo desses indivíduos de forma ativa.…”
Section: Discussionunclassified
“…A number of scientists found "Pilates" system's positive influence on physical fitness of second mature and elderly women: increase of flexibility, strength, power endurance and coordination indicators [23,26,27].…”
Section: Discussionmentioning
confidence: 99%